Discussion of "Experiences with big data: Accounts from a data scientist's perspective". Issue Volume 32:Issues 4(2020) (1st October 2020) - Coleman, Shirley
Abstract: The authors have produced an excellent essay with many interesting examples based on their broad experience of data analytics. One emerging issue is the fashion for companies, especially SMEs, to employ a token or trophy data scientist; this practice can lead to a dangerous watering down of data science. Descriptive analysis of big data can lead to insight, however when corresponding end results are known, the analysis can be much richer and lead to significant impact.